Research on the characteristics of criminal offenses in the field of information and communications - Yuldashev, R.; Kalpeyeva, Z. (Харківський національний автомобільно-дорожній універститет, 2024)
The rapid development of digital technologies and the expansion of internet access in Kazakhstan have led to a surge in cybercrimes, which pose significant risks to society and individuals. This research investigates the characteristics of criminal offenses in the area of information and communications, highlighting trends, legislation, and the role of cybersecurity measures in mitigating these risks. By analyzing data from various sources and evaluating criminal statistics, the paper explores the need for enhanced laws and technological frameworks to address these crimes.
Keywords: Cybercrime; Information Security; Legislation; Criminal Offenses; Cybersecurity